Nonclinical Safety Profile of BMS-986001, a Nucleoside Transcriptase Inhibitor for Combination Retroviral Therapy. (May 2014) - Mausumee, Guha; Frank, Simutis; Shawn, Clark; Dara, Hawthorne; Zhao, Yue; Soleil, Piche Marie; Sanderson, Thomas P.; Michael, Graziano; Marc, Davies
Nucleoside reverse transcriptase inhibitors (NRTIs)/nucleotide reverse transcriptase inhibitors are key components of combination antiretroviral therapy for HIV infection. First-generation NRTIs are associated with mitochondrial toxicity in patients, mainly due to inhibition of human DNA polymerase γ (hDNA polγ) that manifests as adverse events such as lipodystrophy, lactic acidosis, myopathy, cardiomyopathy, or nephropathy in patients. In chronic nonclinical studies in rodents and nonrodents, eukaryotic (host) mitochondrial toxicity manifests as some drug-specific toxicities similar to human toxicity. BMS-986001, a novel thymidine analog with minimal hDNA polγ inhibition, has demonstrated antiretroviral activity in early clinical studies. The primary toxicity of BMS-986001 in rats and monkeys is bone marrow dyserythropoiesis with associated decreases in red blood cell mass. Additionally, at high doses, severe platelet reductions accompanied by cutaneous petechiae began during weeks 8 and 11 in 3 of 60 monkeys in chronic toxicity studies. In a 6-month study, platelet reductions required euthanasia of the 2 affected monkeys (300 mg/kg/d) at week 14, but with dose reduction (200 mg/kg/d) remaining monkeys had no platelet changes. One affected monkey (200 mg/kg/d) in a 9-month study completed dosing and its platelet counts recovered during a 1-month recovery. Formation of platelet-bound immunoglobulin in the presence of BMS-986001, together with rapid and complete platelet recovery in the absence of BMS-986001, suggested that platelet decreases in monkeys may be immune mediated. No findings indicative of mitochondrial toxicity were observed in rats or monkeys given BMS-986001, suggesting an improved safety profile compared to marketed NRTI or tenofovir disoproxil fumarate.